Allergic airway sensitization induces T cell activation but not airway hyperresponsiveness in B cell-deficient mice - Hamelmann, E. (The National Academy of Sciences of the USA, 1997)
B cells play an important role in the allergic response by producing allergen-specific Igs as well as by serving as antigen-presenting cells. We studied the involvement of B cells in the development of responses in a murine model of allergic airway sensitization. Normal and B cell-deficient (μMt(−/−)) B10.BR mice were sensitized via the airways to ovalbumin; Ig production, cytokine elaboration from local lymph node cells, development of airway hyperresponsiveness, and histological changes in the airways were evaluated. Both strains of mice had increased production of T helper 2-like cytokines and developed an accumulation of eosinophils in the bronchial tissue after airway sensitization. However, only wild-type mice produced allergen-specific antibodies and exhibited altered airway function. B cell-deficient mice reconstituted with anti-ovalbumin IgE during the course of sensitization developed increases in airway responsiveness. These results indicated that neither B cells nor IgE were necessary for the induction of a T helper 2-type cytokine response or eosinophil infiltration of the airways after allergic sensitization but that IgE was required as a second signal for the development of airway hyperresponsiveness in this model of airway sensitization.